Qualitative analysis of market paneer of Odisha - Naik, Rabi Ranjan; Pati, Prasad Kumar; Sardar, Kautuk Kumar; Dorai, R. Palani (Indian Journal of Dairy Science, 2016)
Paneer has great value in diet because it is rich source of high quality proteins, fat, minerals and vitamins. Paneer has a short life span of about 5-7 days at refrigeration storage without much deterioration in the quality but freshness of the product is lost after 3 days. So, the present study was carried out to analyze the quality parameters of paneer of various locations of Odisha by evaluate the physical, chemical and microbiological quality of paneer, marketed in shops of Odisha.The moisture content was ranged from 38.51 to 67.00per cent. While for fat content from 11 to 29.21 per cent and for protein content ranged from 12.40 to 21.69 per cent and all samples were analyzed for total viable count (bacteria) on nutrient agar and fungi on PDA. All samples were analyzed for presence of E.coli, Staphylococcus spp, and Salmonella spp. Methylene blue reduction test was also performed. All the 32 samples had bacteriological counts ranging from 1x106 to 7.7 x106 CFU/gm and fungal counts ranging from 1x105 to 6.5 x105 CFU/gm. Of all the samples Staphylococcus spp. was found in 96% of the samples. E.coli in 74% and Salmonella spp were found in 34% of the samples. The heavy bacterial and fungal contamination seen in all samples predominantly Staphylococcus spp. and fecal coliforms can be attributed to poor hygienic conditions during paneer preparation, handling and storage. The study suggests the need for more strict preventive and control measures to avoid pre and post process contamination in milk food products.